Preservation of Gut Microbiome Following Ridinilazole vs. Fidaxomicin Treatment of Clostridium difficile Infection. (4th October 2017) - Mitra, Suparna; Chilton, Caroline; Freeman, Jane; Wood, Henry; Quirke, Phil; Taylor, Morag; Vickers, Richard; Wilcox, Mark
Abstract: Background: Clostridium difficile infection (CDI) is a major cause of nosocomial diarrhea associated with antimicrobial-mediated dysbiosis. Dysbiosis may be perpetuated by antibiotic (AB) CDI therapy, leading to recurrent CDI. Ridinilazole (RIDI) has very narrow activity against certain clostridia. We measured faecal microbiomes of Phase 2 subjects randomised to 10 days of RIDI or fidaxomicin (FDX) for CDI. Methods: Fecal samples (27 patients) were obtained at study entry (DM1-D1), Day 2 (D2-D3), Day 5 (D4–5), Day 7 (D5–7), Day 10 (D9–10), Day 12 (D11–14), Day 25 (D15–25), D30 (D25–30), Day 40 (D40+) and grouped according to blinded treatment (Drug A or B). DNA was extracted using the QIAamp DNA Stool Mini Kit (Qiagen), and 16S V4 PCR products sequenced on an Illumina MiSeq®. Samples were analyzed as a full dataset ( n = 154) and as subgroups: no concomitant (con)AB or prior CDI AB ( n = 67); no conAB but prior CDI AB ( n = 44); total no conAB ( n = 111). Data were quality controlled and annotated (QIIME, Usearch, Greengenes, PyNAST, RDP). OTU files were imported in MEGAN for further analyses. Results: Comparable sustained clinical response rates to 30 days post end of therapy were seen with RIDI (50%) compared with FDX (46.2%); estimated treatment difference 2.9% (95% CI −30.8, 36.7). Following unblinding (drug A = RIDI, drug B=FDX), Simpsons diversity indices showed marked microbiome differences at family level for RIDI vs. FDX subjects in multiple analyses. This was most marked for no conAB or prior CD AB and total no conAB subjects, in whom RIDI microbiome diversity was markedly greater (approaching significance) during CDI treatment and significantly greater at D11-D14 and D4–5, D6–8, respectively ( P < 0.05) (figure). In particular, Bifidobacteriaceae and Ruminococcaceae populations, previously linked to colonisation resistance, were more stable during RIDI treatment. Conclusion: RIDI preserved gut microbiome diversity to a greater extent than FDX during CDI treatment. Differences were most marked for, but not restricted to, patients receiving no conAB. Microbiome sparing by RIDI is consistent with low CDI recurrence rates. Disclosures: C. Chilton, Astellas: Investigator and Speaker's Bureau, Research grant and Speaker honorarium. Da Volterra: Investigator, Research grant. Paratek pharmaceuticals: Investigator, Research grant. Actavis: Investigator, Research grant; J. Freeman, Astellas: Investigator, Research grant. Morphochem: Investigator and Research Contractor, Research support. Melinta: Research Contractor, Research support. R. Vickers, Summit plc: Employee, share options; M. Wilcox, Merck & Co., Inc.: Consultant, Consulting fee. Cubist: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Grant recipient and Speaker honorarium. Alere, Actelion Pharma, Astellas, Optimer, sanofi pasteur, Summit Pharma, bioMerieux, Da Volterra, Qiagen, Cerexa, Abbott, AstraZeneca, Pfizer, Durata Therapeutics, Seres Therapeutics, Valneva, Nabriva Therapeutics, Roche, The Medicines Company, Basilea P: Consultant, Consulting fee. Alere, Actelion Pharmaceuticals, Pharmaceuticals, Astellas, Optimer Pharmaceuticals, sanofi pasteur, Summit Pharmaceuticals, bioMerieux, Da Volterra, Qiagen, Cerexa, and Abbott: Grant Investigator, Grant recipient.